Dampak Polusi Mikroplastik dalam Air Minum Rumah Tangga terhadap Gangguan Kesehatan Gastrointestinal - Fendi Azhari; Heri Sopian; Nailil Ula (Journal of Medical and Health Science, 2026)
Microplastic pollution has become a global environmental issue that is gaining increasing attention due to its potential impacts on human health. One of the main routes of microplastic exposure is through household drinking water consumption. This study aims to analyze the presence of microplastics in household drinking water and examine its relationship with gastrointestinal health disorders in the community. This study used an observational analytical design with a cross-sectional approach. Data were collected through household drinking water sampling and a health survey of respondents who use the water source. Laboratory analysis was conducted to identify the presence, shape, size, and type of microplastics in the water samples using filtration and microscopic identification methods. Respondent health data were obtained through structured interviews using a questionnaire containing information on respondent characteristics and gastrointestinal complaints experienced. The results showed that microplastics were found in most household drinking water samples, characterized by plastic fragments and synthetic fibers of varying sizes. The most frequently reported gastrointestinal complaints by respondents included abdominal pain, indigestion, diarrhea, and constipation. Data analysis indicated a trend towards an association between exposure to microplastics in household drinking water and an increased incidence of gastrointestinal health disorders. These findings suggest that microplastics in drinking water have the potential to be a risk factor affecting community gastrointestinal health. Therefore, efforts to control plastic pollution and improve the quality of drinking water management are important steps in protecting public health from exposure to microplastics.